Fecal Calprotectin in Cystic Fibrosis and Its Relation to Disease Parameters: A Longitudinal Analysis for 12 Years. Issue 4 (October 2017) - Ellemunter, Helmut; Engelhardt, Alexander; Schüller, Katharina; Steinkamp, Gratiana
ABSTRACT: Objectives: Fecal calprotectin (FC) is a marker of inflammation in the intestinal tract. We assessed FC levels longitudinally in patients with cystic fibrosis (CF) and evaluated the relation between FC results and relevant markers of disease. Methods: Calprotectin was measured in fecal samples starting in 2003 and values were stored in the center's patient database. In this retrospective analysis, we searched for associations of FC concentrations with disease severity and progression. Linear mixed effects models were used to model the logarithm of FC levels. Results: A total of 171 patients (0–61 years) had 2434 FC measurements between 2003 and 2015, with a total observation period of 1686 patient-years. Median (interquartile range) FC concentrations were 60.9 (75.9) μg/g and 61% of the samples showed elevated FC concentrations (>50 μg/g). Despite some statistically significant effects, there was no clinically relevant association among FC and sex, age, forced expiratory volume in 1 second z score, or body mass index z score. Pancreatic insufficiency (ie, fecal elastase <100 μg/g stool) was associated with considerably higher FC values compared to normal pancreatic function (median FC 68 vs 29 μg/g, P < 0.0001). F508del homozygous subjects showed a trend to higher FC values than heterozygous patients (median 71 vs 62 μg/g, P = 0.173). In addition, a significant association with increasing serum C-reactive protein concentrations ( P < 0.0001) was observed. Conclusions: FC was elevated in two-thirds of stool specimens. Increased FC was more common in patients with pancreatic insufficiency. Whether increased FC reflects intestinal inflammation in patients with CF remains to be determined. Abstract : Supplemental Digital Content is available in the text